Success and Failure of IS/IT Projects A State of the Art Analysis and Future Directions - Hughes, D. Laurie; Dwivedi, Yogesh K.; Simintiras, Antonis C.; Rana, Nripendra P. (SpringerBriefs in Information Systems, 2016)
This book examines the link between change and project management and how creating a closer alignment between these two methodologies can yield greater benefits and mitigate elements of failure of information systems (IS) projects. This study explores the underlying challenges and practicalities of closer integration of the two disciplines and asserts that such a successful change goes beyond the simple training of project managers in the practitioner context. Instead, it requires organizations to conceptualize the necessary challenges to realize the potential benefits of this recommended integrated approach. The integration of both project and change management has been advocated in existing research, but the challenges of moving from a current position of separate methodologies, different standards bodies and in some cases totally separate organizational structures, is a step change for many organizations. Change initiatives where good change management practices are implemented, can increase the probability of successful organizational change. The tasks of leading and sustaining change can be complex and often entail the interplay of multiple factors involving action by people at every level of the business. This book offers a guide that identifies the barriers and major challenges that may arise in the development of the closer integration of change and project management. With a better understanding of these issues, organizations can avoid such pitfalls when establishing their own integrated approach.